Republic of Kazakhstan : 2015 Article IV Consultation-Press Release; Staff Report for the Republic of Kazakhstan. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that against the backdrop of external shocks, economic growth and inflation in Kazakhstan have decelerated. Financial conditions have tightened, and external imbalances are emerging. Real GDP growth slowed to an annualized 2 percent during the first quarter of 2015, down from about 4 percent in 2014 and 6 percent in 2013. In addition to weaker external demand, slower growth was driven by the impact of lower income and profitability and confidence effects on private consumption and domestic investment. Real GDP growth is projected to decelerate to 2 percent in 2015, owing to weaker demand from Russia and China, lower oil prices, confidence effects, and continuing delays in the Kashagan oil field.